AKURASI METODE CONCORDANCE BERDASARKAN PANJANG TES DAN UKURAN SAMPEL - Nahason Sitohang (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2016)
The objective of this research is to evaluate the industrial work practice program of students of Public Vocational Middle School. The Discrepancy Evaluation Model (DEM) used in this research is supported by data collection techniques consisting of observation, interview, distribution of questionaires, and related document compilation. Data analysis is carried out in line with the aspects which must be evaluated (comprising definition, installation, process, and product) and the evaluation criteria. The research’s findings showed that the program had quite clear regulation basis with installation prepared by the goverment, good process, and has a difference gap allowing correction to be made in the future. Based on the findings, it can be concluded that the work practice program at the various industries in Public Vocational Middle School had been implemented properly.